Striatal responses to Negative Monetary Outcomes Differ between Temperamentally Inhibited and Non-inhibited Adolescents - Helfinstein, Sarah M. (2010)
The present study compared blood oxygen level dependent (BOLD) response in behaviorally inhibited and behaviorally non-inhibited adolescents to positive and negative feedback following their choice in a reward task. Previous data in these same subjects showed enhanced activation in striatal areas in behaviorally inhibited subjects to cues predicting gain or a loss. However, no analyses had examined responses following actual gains or losses. Relative to non-inhibited subjects, behaviorally inhibited subjects in the current study showed enhanced caudate response to negative but not positive feedback, indicating that striatal sensitivity to feedback may be specific to aversive information. In addition, compared to non-inhibited subjects, behaviorally inhibited subjects exhibited reduced differentiation between positive and negative feedback in ventromedial prefrontal cortex (vmPFC). This suggests a perturbed ability to encode reward value.